Penerapan Permainan Monopoli untuk Meningkatkan Perkembangan Bahasa pada Anak Speech Delay - Ashari, Novita; Ayu Lestari Natsir, Tri; Dilla AT, St. Hajar; Nurzhafirah (NANAEKE: Indonesian Journal on Early Childhood Education, 2024)
Speech delay is a condition where there is repetition of words, phrases, or sentences in other people's speech. These conditions cause delays in language development in children. This study's purpose is to apply Monopoly games to improve language development in group B speech-delayed children at Aisyiyah 5 Parepare Kindergarten. The method used by researchers in this research is the descriptive qualitative method. Data collection techniques in this study are interview techniques, documentation, and observation. This research was conducted at TK Aisyiyah 5 Parepare. Subjects in this study were 6-year-old females. The subjects in this study were 8 female children and 7 children male. The subject is in group B at Kindergarten Aisyiyah 5, where there are 15 children in the class. The results of the study show that aspects of AN language development have not yet been developed. When conducting research using the Monopoly game, The researcher switched the game to a game of guessing the picture on a Monopoly game card. This happened because AN's condition had difficulties in understanding language, expressing language, and literacy.